"My Grandfather kept one of these tins on top of the bookshelf": Consumers' recalled experiences involving packaging. Issue 1 (11th January 2016) - Ryynänen, Toni; Joutsela, Markus; Heinonen, Visa
Abstract : Purpose: – This explorative paper aims to identify the dimensions of recalled consumption experiences involving packaging by means of interpretive analysis. Scholarly interest towards experiential aspects of consumption started in the beginning of 1980s. Design/methodology/approach: – The memory-based research materials were collected from 97 Finnish consumers within a two-day weblog session. The consumers were asked to describe personally meaningful packaging-related experiences and to submit a photograph of the relevant packages. The analysis focused on common dimensions associated with the described meaningful experiences. Findings: – The authors built a conceptual framework incorporating "nostalgic" and "accessible" experiences. The dimensions of nostalgic experience, which although anchored in the present can be re-lived only in the memory, include the involvement of key persons; the places and physical spaces in which the experience happened; and actions or practices involving packaging during an experience. Accessible experiences include the following dimensions: lasting product and packaging encounters; individual personal experiences; culturally meaningful celebrations and rituals; and packaging that appeals to the senses. It is proposed that meaningful consumption experiences involving packaging may reflect both nostalgic and accessible dimensions. Originality/value: – Although there is a growing interest towards consumers' role in the packaging value chain, their packaging experiences are addressed rarely. It is proposed that the consumption experiences involving packaging are a mix of nostalgic and accessible dimensions.